Analysis Sector Economy With The Shift Share Method And Policy Strategy Growth And Competitiveness Through Collaborative Governance - Abdul Haliq; Sitna Hajar Malawat; Ridwan Sya'rani; Deli Anhar (Sean Institute, 2025)
The purpose of this study is to analyze the growth and competitiveness of the economic sector or business field in Barito Kuala Regency, as well as policy strategies for increasing the growth and competitiveness of the economic sector through collaborative governance. The method used is quantitative descriptive with Shift-Share Analysis (SSA), the source of data analysis is the current price GRDP according to the business field in 2019 and 2023 in Barito Kuala Regency and South Kalimantan Province. The study results show that not all economic sectors are included in the Shift-Share Analysis (SSA) quadrant. Quadrant I: Fast Growth and Competitive; no economic sectors or business fields were found. Quadrant II: Slow Growth and Competitive; there are economic sectors 1) Water Supply, Waste Management, Waste, and Recycling; 2) Construction; 3) Wholesale and Retail Trade; Car and Motorcycle Repair; 4) Real Estate; 5) Government Administration, Defense and Compulsory Social Security; and 6) Education Services. Quadrant III: Rapid Growth and Uncompetitive, economic sectors 1) Mining and Quarrying, and 2) Transportation and Warehousing. Quadrant IV: Slow Growth and Uncompetitive, economic sectors 1) Agriculture, Forestry, and Fisheries; 2) Manufacturing Industry; 3) Electricity and Gas Supply; 4) Accommodation and Food and Beverage Provision; 5) Information and Communication; 6) Financial Services and Insurance; 7) Corporate Services; 8) Health Services and Social Activities; and 9) Other Services. Policies to increase growth and competitiveness of the economic sector through collaborative governance based on the main variables 1) Human Resources, 2) MSME Development, 3) Product Marketing, and supporting variables 1) Infrastructure Development, and 2) Innovation and Technology.